Application of the Quantum Teaching Method in Improving Student Learning Outcomes in Class 5 Social Studies at SD Negeri Bener 01 Academic Year 2015/2016 - Cahyanto Aris; Tukiran Tukiran (Proceedings Series on Social Sciences & Humanities, 2023)
In the implementation of classroom learning, it turns out that there are still many students who do not meet the KKM, this is possible because the teacher uses inappropriate methods, for example the teacher only uses teaching materials and methods that are mastered. So that most students do not understand the actual subject matter and their learning outcomes are low. This condition was experienced by teachers at SD Negeri Benar 01, Majenang District, Cilacap Regency. The purpose of this Classroom Action Research (CAR) is to find out how far student learning outcomes have increased and to determine subject matter through the application of the Quantum Teaching Method. In this Classroom Action research it was carried out in 3 cycles, from the results of the Actions taken it was proven to increase student learning completeness. From 64.29% in the first cycle, it can increase to 72.43% in the second cycle, and 80.71% in the third cycle. The results of this action research show that the application of the Quantum Teaching Method in public elementary schools is correct 01.